Polymers in Lithium‐Ion and Lithium Metal Batteries. Issue 15 (25th January 2021) - Li, Junheng; Cai, Yifeng; Wu, Haomin; Yu, Zhiao; Yan, Xuzhou; Zhang, Qiuhong; Gao, Theodore Z.; Liu, Kai; Jia, Xudong; Bao, Zhenan
Abstract: Lithium‐ion batteries play a significant role in modern electronics and electric vehicles. However, current Li‐ion battery chemistries are unable to satisfy the increasingly heightened expectations regarding energy demand and reliability. To boost the overall energy density while ensuring the safety of Li batteries, researchers have focused on alternative battery materials, such as silicon, sulfur, and Li metal. These represent promising avenues, although numerous obstacles (e.g., Si cracking, polysulfide shuttling, Li dendrites, etc.) must be tackled before batteries based on these materials can enter mass production and penetrate the mainstream market. Polymers are a class of materials that are widely used in current battery systems; however, many novel polymer chemistries may offer better performance and reliability than the current ones, and even overcome the issues of the above‐mentioned new battery materials. In this review, selected polymeric materials for solving these issues are categorized into four parts: polymer electrolytes, polymer artificial solid‐electrolyte interphases, binders, and separators. Both the current progress and the characterization methods are included. Potential future directions of energy materials research are pointed out as well. Abstract : This review outlines the polymers used in lithium batteries and categorizes them into four sections: 1) solid polymer electrolytes, 2) polymer artificial solid electrolyte interphases, 3) binders, and 4) separators. Detailed examples, summary, and outlook are provided. Particularly, this review incorporates the experience from the battery industry and shows an organic combination between academia and industry.